1964
DOI: 10.1136/jcp.17.3.292
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age on normal values of the Westergren sedimentation rate

Abstract: SYNOPSIS Westergren sedimentation rates were done on 603 healthy blood donors. The results showed an increase in the normal values with age. The normal values found in this series were higher than those generally accepted as normal.The commonly accepted normal values for the Westergren method of determining the sedimentation rate (E.S.R.) are 3-5 mm. in the first hour for males and 7-12 mm. for females (Whitby and Britton, 1963). During routine blood testing we found a number of apparently normal persons whos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

1967
1967
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 3 publications
1
8
0
1
Order By: Relevance
“…The tendency for the ESR to rise with age is well known (Ansell and Bywaters, 1958;Dawson, 1960;Boyd and Hoffbrand, 1966). Our results (Table I) confirm this and indicate a tendency for the rise to flatten out after age 60 (Hilder and Gunz, 1964). There was a considerable fluctuation in mean value from month to month, but a general pattern of high values in spring and autumn and low values in summer appeared (Table II).…”
Section: Statistical Resultssupporting
confidence: 84%
“…The tendency for the ESR to rise with age is well known (Ansell and Bywaters, 1958;Dawson, 1960;Boyd and Hoffbrand, 1966). Our results (Table I) confirm this and indicate a tendency for the rise to flatten out after age 60 (Hilder and Gunz, 1964). There was a considerable fluctuation in mean value from month to month, but a general pattern of high values in spring and autumn and low values in summer appeared (Table II).…”
Section: Statistical Resultssupporting
confidence: 84%
“…The association of older age with higher sCD14 concentrations in this study is highly consistent with similar age-related changes reported in the expression of other acute-phase reactants. Age-related increases have been shown for ESR in addition to a number of specific acute-phase proteins including fibrinogen, alpha-1-anti trypsin, haptoglobin, and others 42,43,44 .…”
Section: Discussionmentioning
confidence: 97%
“…All were free from symptoms of chronic and intercurrent disease and had a blood sedimentation rate (Westergren) in the normal range (Hilder & Gunz, 1964). Control activator levels were obtained from patients convalescent from a variety of minor disorders which have been found not to affect fibrinolytic activity.…”
Section: Normal Valuesmentioning
confidence: 99%